2015
DOI: 10.1186/s13002-015-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoveterinary plants and practices used for ecto-parasite control in semi-arid smallholder farming areas of Zimbabwe

Abstract: BackgroundThe inclusion of traditional plant-based ecto-parasite control methods in primary health care of livestock is increasingly becoming an important intervention for improving livestock productivity in resource-challenged smallholder farming areas. In this study, commonly used plants used for the control of cattle ticks and other pests were identified through a survey in four semi–arid districts of Zimbabwe.MethodsA standard structured questionnaire with details of demographics, socioeconomic status of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 29 publications
(35 reference statements)
3
48
1
Order By: Relevance
“…Scientific studies on L. javanica indicate that it has a wide range of pharmacological activities (Table 4), which include anticancer [140], antidiabetic [141], antimalarial [4, 49, 142], antimicrobial [2, 3, 7, 17, 7375, 77, 83, 84, 126, 143], antioxidant [7, 10, 11, 75, 77, 125], antiplasmodial [2, 79, 80, 84, 144, 145], and pesticidal effects [1, 2, 59, 95, 120, 146–150] and cytotoxicity [2, 73, 79, 120] activities. Table 4 summarizes some of the pharmacological studies undertaken on L. javanica extracts aimed at evaluating some of the ethnomedicinal uses of the species documented throughout its distributional range (see Table 1).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific studies on L. javanica indicate that it has a wide range of pharmacological activities (Table 4), which include anticancer [140], antidiabetic [141], antimalarial [4, 49, 142], antimicrobial [2, 3, 7, 17, 7375, 77, 83, 84, 126, 143], antioxidant [7, 10, 11, 75, 77, 125], antiplasmodial [2, 79, 80, 84, 144, 145], and pesticidal effects [1, 2, 59, 95, 120, 146–150] and cytotoxicity [2, 73, 79, 120] activities. Table 4 summarizes some of the pharmacological studies undertaken on L. javanica extracts aimed at evaluating some of the ethnomedicinal uses of the species documented throughout its distributional range (see Table 1).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…These authors found no parasites on microscopic examination of the Giemsa-stained thin blood smear collected from treated cattle implying that the animals did not suffer from clinical tick-borne diseases. Similarly, Nyahangare et al [59] tested the pesticidal activity of L. javanica water extracts against cattle ticks. The authors found no significant difference between cattle treated with a commercial synthetic acaricide and those under L. javanica treatment.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results of certain studies suggest that environmentally friendly acaricides can be obtained from plants (GHOSH et al, 2011;GARCIA et al, 2012). As an alternative, plant extracts are used to manage animal health and parasite control in several regions in the world (GITHIORI et al, 2006;TAMIRU et al, 2013;NYAHANGARE et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in Pakistan, only a handful number of plants have been used against R. microplus (Zaman et al, 2012a;Sindhu et al, 2012;Nawaz et al, 2015) in contrast to more extensive investigations elsewhere (Chen et al, 2011;dos Santos et al, 2013;Nyahangare et al, 2015;Fouche et al, 2016a,b (Chagas et al, 2016;Vudriko et al, 2016). Briefly, larvae were inserted into drug impregnated filter paper for 24 hrs at certain temperature (27-29°C) and relative humidity (80-85%).…”
Section: Plants Used As Acaricidesmentioning
confidence: 99%